Effect of 1-ethyl-3-methylimidazolium nitrate on the electrical properties of starch/chitosan blend polymer electrolyte - Khiar A.S.A.; Anuar M.R.S.; Md. Parid M.A. (Trans Tech Publications Ltd, 2024)
Indexed by Scopus